(untitled) (International Seven Journal of Multidisciplinary, 2024)
This article discusses the construction of knowledge from the perspective of maker culture, highlighting the role of active methodologies in youth protagonism. Initially, the principle of meaningful learning is addressed, which emphasizes the incorporation of new concepts into students’ prior knowledge. Next, Brazilian legislation related to education is presented, highlighting the role of the State and the family in promoting the full development of young people. The text also discusses the evolution of pedagogical practices, moving from Traditional Pedagogy to active methodologies, which place the student as the protagonist of the learning process. The National Common Curricular Base (BNCC) is mentioned as an important reference for implementing these approaches. Finally, some of the most effective active methodologies are presented, such as project-based learning, the flipped classroom, cooperative learning and hybrid teaching, highlighting their relevance for developing 21st century skills and promoting a more meaningful and inclusive education.